Progress in understanding colour confinement - Biagio Lucini (Nuclear Physics B - Proceedings Supplements, 1998)
New results from lattice are presented,which demonstrate that monopoles condense in the vacuum of confined phase of QCD, which is thus a dual superconductor. Monopoles defined by different abelian projections appear to be physically equivalent.